2014
DOI: 10.1186/1477-7819-12-58
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative platelet lymphocyte ratio (PLR) is superior to neutrophil lymphocyte ratio (NLR) as a predictive factor in patients with esophageal squamous cell carcinoma

Abstract: BackgroundRecent studies have shown that the presence of systemic inflammation correlates with poor survival in various cancers. The aim of this study was to determinate the prognostic value of the neutrophil lymphocyte ratio (NLR) and the platelet lymphocyte ratio (PLR) in patients with esophageal squamous cell carcinoma (ESCC).MethodsPreoperative NLR and PLR were evaluated in 483 patients undergoing esophagectomy for ESCC from January 2005 to December 2008. The prognostic significance of both markers was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
228
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(239 citation statements)
references
References 16 publications
(23 reference statements)
5
228
1
5
Order By: Relevance
“…However, in contrast to the previous studies, NLR wasn't statistically significant in terms of being an independent factor in the differentiation of early and advanced-stage diseases and thus was not influential in prognosis (Table 2). NLR and PLR have also been become popular in many studies about cancers (Miglani et al, 2013;Unal et al, 2013;Acmaz et al, 2014;Feng et al, 2014;Tanoglu et al, 2014). PLR was found to have a better prognostic performance among other blood components such as platelet number and NLR.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to the previous studies, NLR wasn't statistically significant in terms of being an independent factor in the differentiation of early and advanced-stage diseases and thus was not influential in prognosis (Table 2). NLR and PLR have also been become popular in many studies about cancers (Miglani et al, 2013;Unal et al, 2013;Acmaz et al, 2014;Feng et al, 2014;Tanoglu et al, 2014). PLR was found to have a better prognostic performance among other blood components such as platelet number and NLR.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is an index of systemic inflammation and has been identified as a prognostic factor in patients with CRC and gastric cancer (24,25). However, serum CRP levels are not routinely assessed in the pre-operative assessment (12,14,18). Instead, NLR and PLR, calculated from leukocyte differential counts and platelet counts, respectively, are more readily available and inexpensive compared to CRP (7).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the scope and effects of an inflammatory reaction have always been assessed according to a number of biochemical markers, including the neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR), which are inexpensive markers of systemic inflammation (7). Previous studies have indicated that elevated NLR or PLR suggested a poor prognosis for various types of cancer, including ovarian (8), breast (9,10), non-small cell lung (11), esophageal (12,13), gastric (7,14), hepatocellular (15) and CRC (2,(16)(17)(18). However, the current literature leaves certain questions unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…6,10 En algunos estudios se informó que el aumento del recuento de trombocitos y la reducción del recuento de linfocitos están asociados con tumores malignos, arteriopatía coronaria y diversas enfermedades inflamatorias. 9,14,15 Feng y col. informaron que el ITL estaba asociado con una sobrevida menor en los casos de cáncer esofágico. 14 Acmaz y col. demostraron que el ITL estaba elevado en los pacientes con cáncer de endometrio en comparación con los sujetos del grupo de referencia e informaron que este marcador inflamatorio también puede usarse para el diagnóstico.…”
Section: Discussionunclassified
“…9,14,15 Feng y col. informaron que el ITL estaba asociado con una sobrevida menor en los casos de cáncer esofágico. 14 Acmaz y col. demostraron que el ITL estaba elevado en los pacientes con cáncer de endometrio en comparación con los sujetos del grupo de referencia e informaron que este marcador inflamatorio también puede usarse para el diagnóstico. 15 En el estudio actual, el ITL era significativamente más alto en los pacientes con mordedura de serpiente que en los sujetos sanos del grupo de referencia.…”
Section: Discussionunclassified